Meningkatkan Hasil Belajar dan Keaktifan Melalui Game Rangking 1 Dengan Materi Umum Bersama Anak Panti Asuhan As-Sohwah - Ningrum, Andri Eka Kusuma Ningrum; Ervilda, Hafifah; Afrinaldi, Afrinaldi; Oktamade, Dion; Hidayat, Muhammad Syafik; Andrizal, Gilang Fikri; Suci, Rama Gita (LPPM UMRI, 2021)
The purpose of holding a rank 1 game is to test improving learning outcomes and the activeness of the children of the As-Shohwah orphanage. This 1st rank game was held at the elementary-junior-high school level, the 1st rank was held at the As-Shohwah Orphanage, Simpang Baru Village, Pekanbaru City. Team held a ranking 1 game method by providing training and then giving a competition in the form of general questions. The results of the 1st rank game in children get enthusiastic, increased interest in learning again, lively and active enthusiasm in answering questions in the 1st rank game play.